Alcoholic steatohepatitis - Stickel, Felix; Seitz, Helmut K. (Best practice & research. Clinical gastroenterology, 2010)
Severe alcoholic steatohepatitis has a poor prognosis and is characterized by jaundice and signs of liver failure. Its incidence is unknown, but prevalence is around 20% in cohorts of alcoholics undergoing liver biopsy. Diagnosis is established with elevated liver transaminases, neutrophil counts, serum bilirubin, and impaired coagulation and a history of excessive alcohol consumption, and exclusion of other etiologies. Histology is helpful but not mandatory. Prognostic scores include the Maddrey’s discriminant function, the model of end-stage liver disease, and the Glasgow Alcoholic Hepatitis Score. Pathophysiology involves hepatic fat storage, increased hepatic uptake of gut-derived endotoxins triggering Kupffer cell activation and release of proinflammatory triggers, induction of cytochrome P4502E1 producing toxic acetaldehyde and reactive oxygen species, and ethanol-mediated hyperhomocysteinemia causing endoplasmic reticulum stress. Treatment includes abstinence, enteral nutrition, corticosteroids, and possibly pentoxifylline. A debate is ongoing whether certain patients with severe alcoholic steatohepatitis could be eligible for liver transplantation.